Pensabitan Makna dalam Perbahasan Epistemologi Ahli Sunah Waljamaah: Affirmation of Meaning in the Epistemological Discourse of Ahl al-Sunnah wa al-Jama’ah - Kamis, Maryam Habibah; Wan Ramli, Wan Adli; Hamat, Mohd Fauzi (Afkar: Jurnal Akidah dan Pemikiran Islam, 2025)
The first principle of the creed of Ahli Sunnah wa al-Jama‘ah is affirmation of the meaning of reality and knowledge. This affirmation of the meaning of reality and knowledge is discussed at the beginning of Usul al-Din by Abu Mansur al-Baghdadi, who represents the Ahl al-Sunnah wa al-Jama‘ah tradition, stating that the meaning of reality and knowledge of things can be firmly established. However, Muslim liberal thinkers such as Abou El Fadl, Ebrahim Moosa, Abdul Karim Soroush, and Zainah Anwar present differing conceptions towards affirmation of meaning. Their views are influenced by postmodernist thought that upholds epistemic doubt (scepticism), truth as limited by individual perspective (subjectivism), and the rejection of absolute truth (relativism). This study demonstrates that the affirmation of meaning is indispensable within Islamic epistemology. The absence of such affirmation would fail the cognition of the knower, thereby preventing it from constituting valid knowledge.